ANALISIS STRUKTURAL TERHADAP CERITA SELAT NASI SASTRA LISAN MASYARAKAT KECAMATAN SUBI KABUPATEN NATUNA - Melianti, Melianti; Sulissusiawan, Ahadi; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to determine the structure or intrinsic elements of the Nasi Strait folklore from Subi District, Natuna Regency. Research methods used is descriptive with the form of qualitative research. Data source this research is Mr. Alfian and the data is a tangible structure quote words, phrases, sentences, and paragraphs. The results of this study are first: figures from the Nasi Strait folklore, there is 1 central character and 12 additional characters consisting of 2 mainstay characters, 5 additional characters, and 5 background characters. In terms of character, there are 4 round characters consisting of 13 characters and 9 simple characters consisting of 9 characters. Second: there are 5 parts to the stages of the flow, namely exposure, wiring, ascent, climax, and separation. Third: there are 33 settings consisting of 8 place settings, 11 time settings, 8 atmosphere settings, and 5 social settings. Fourth: the theme contained in the Nasi Strait folklore is disappointment. Fifth: the message contained in this Nasi Strait folklore is about don"™t nover break a promise that has been agreed.